2017
DOI: 10.1007/s11136-017-1771-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among parents of preterm infants: a scoping review

Abstract: Standardizing the operationalization of the QoL when analysing mothers and fathers of preterm infants calls for a structured questionnaire adapted to their specific needs. Further research should include both mothers and fathers, invest in mixed methods approaches and be performed in different countries and settings for allowing integration and comparison of findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 55 publications
2
28
0
1
Order By: Relevance
“…The gestational age at which women gave birth was also identified as a risk factor for a worse QoL score, which agrees with other studies [22,33].…”
Section: Discussionsupporting
confidence: 91%
“…The gestational age at which women gave birth was also identified as a risk factor for a worse QoL score, which agrees with other studies [22,33].…”
Section: Discussionsupporting
confidence: 91%
“…4,25 Moreover, preterm birth has a major impact on the quality of life of parents and families. 4,26 Preterm labor is a syndrome 27e33 associated with multiple etiologic processes such as infection/ inflammation, 34e44 vascular disorders, 45,46 decidual senescence, 47e51 uterine overdistention, 52e55 decline in progesterone action, 56e60 cervical disease, 61e65 breakdown of maternalfetal tolerance, 66e68 premature activation of the fetal immune system, 67,69 and maternal stress, 31,70,71 among others. Genetic and environmental factors contribute to each etiology of the preterm labor syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Issues mentioned in the literature such as urinary incontinence and other common health problems may affect HRQoL [5,6,7,8,9,10,11,12,13]. In addition, women’s HRQoL after childbirth may be affected by factors related to pregnancy and delivery [12,14,15], by infant’s health [16], and by non-medical factors, such as race, maternal age, and socioeconomic status [10,17,18]. For example, Oliveira et al found that mothers who were white, 30–40 years of age, and had relatively high education were more likely to report relatively good HRQoL [10].…”
Section: Introductionmentioning
confidence: 99%